Предмет: Математика, автор: welsikor223

-2/5-(-3/5) -3/7-(-3/5) -3/7-(+4/7​

Приложения:

Ответы

Автор ответа: сок111213
1

 -  \frac{2}{5}  - ( -  \frac{3}{5} ) =  -  \frac{2}{5}  +  \frac{3}{5} =  \frac{1}{5}   \\  -  \frac{3}{7}  - (  + \frac{ 4}{7} ) =  -  \frac{3}{7}  -   \frac{4}{7}  =  -  \frac{7}{7}  =  - 1 \\  -  \frac{1}{9}  - ( +  \frac{2}{9} ) =  -  \frac{1}{9}  -  \frac{2}{9}  =  -  \frac{3}{9}  =  -  \frac{1}{3}

Похожие вопросы
Предмет: Физика, автор: dashafedorovich52
Предмет: Математика, автор: Дико020